ON THE ISSUE OF PSYCHOLOGICAL SAFETY OF INCLUSIVE EDUCATIONAL ENVIRONMENT - Maria Igorevna Kirillova (Вестник Северо-Кавказского федерального университета)
The article considers psychological and pedagogical aspects of safety of inclusive educational environment. Disabled children are a special category of children in need of psychological and pedagogical support. The aim of secondary school is to create conditions for barrier-free environment for the children of this category.